Impact of Alcoholism on Teachers' Job Performance in the Schools of Kitwe Town Council Ruhaama East Constituency Ntungamo District. - Ayebare, Joshua (Kabale University, 2024)
This study aimed to investigate the impact of alcoholism on teachers' job performance in schools, focusing on the causes, effects, and potential solutions to alcoholism in Kitwe Town Council, Ruhaama, Ntungamo District. The study is guided by specific objectives, including identifying the causes of alcoholism among teachers in Kitwe Town Council, examining the effects of alcoholism on teachers' job performance, and exploring measures implemented to reduce alcohol consumption in the area. A descriptive research design was used, with a simple random sampling method to select participants. A total of 136 respondents participated in the study. Data were analyzed and presented using statistical methods, with percentages incorporated into tables. The findings revealed that alcoholism has several negative effects on teachers' job performance, and there are multiple factors contributing to alcoholism.